Faktor-Faktor yang Mempengaruhi Balita Stunting di Puskesmas Kampung Guci Menggunakan Regresi Probit Biner - Pratama, Lisya; Helma, Helma (Journal of Mathematics UNP, 2024)
A toodler who is stunted will be shorter than a typical toddler in both height and length. Stunting result in pathological alterations marked by growth that are outside of what is expected, having both short and long term effects. Utilizing binary probit regression, this research attempts to determine the srtucture of the model, the variables that have the highest probability of stunting, and the causes (factors) that cause toodler stunting in Puskesmas Kampung Guci. This research is applied research. This research uses primary data from a sample of 85 toddlers using the accidental sampling technique. According to research findings, exclusive breastfeeding, immunization, healthy latrines, and comorbidities are the variables (factors) that effect toddler stunting at the Puskesmas Kampung Guci.